Retraction: “Success factors of entrepreneurs: Empirical evidence from Serbia” published in 2011 (volume 39, issue 2, p. 15-27) - Board, Editoral (Industrija, 2014)
At the initiative of the editors of journal Industrija and without an agreement of the authors, the article by Stefanović I., Ranković Lj. and Prokić S. is being retracted due to high level of self plagiarism.